2004
DOI: 10.1080/09546630410033772
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation with Evelle® improves skin smoothness and elasticity in a double‐blind, placebo‐controlled study with 62 women

Abstract: Evelle can potentially improve visible signs of cutaneous ageing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 18 publications
4
34
0
3
Order By: Relevance
“…In one study, 55% of participants reported frequent incidence of loose stools (1-3 times daily) after consuming a high dose of squalene (27g/day) [31]. In another study by Segger et al [37] four out of the 58 participants reported gastric discomfort after taking an oral supplement which contained Pycnogenol (10 mg), vitamin C (30 mg), vitamin E (5 mg), biotin (75 mg), selenium (25 mg), zinc (7.5 mg), bio-marine complex (50 mg), horsetail and dietary carotenoids (34 mg) and did not continue with the study. A further study [25] reported side effects of loose stools and upper respiratory tract infection after consuming either two supplement tablets daily which included 250mg green tea polyphenols or from having the placebo capsules.…”
Section: Side Effects/adverse Eventsmentioning
confidence: 99%
See 4 more Smart Citations
“…In one study, 55% of participants reported frequent incidence of loose stools (1-3 times daily) after consuming a high dose of squalene (27g/day) [31]. In another study by Segger et al [37] four out of the 58 participants reported gastric discomfort after taking an oral supplement which contained Pycnogenol (10 mg), vitamin C (30 mg), vitamin E (5 mg), biotin (75 mg), selenium (25 mg), zinc (7.5 mg), bio-marine complex (50 mg), horsetail and dietary carotenoids (34 mg) and did not continue with the study. A further study [25] reported side effects of loose stools and upper respiratory tract infection after consuming either two supplement tablets daily which included 250mg green tea polyphenols or from having the placebo capsules.…”
Section: Side Effects/adverse Eventsmentioning
confidence: 99%
“…Of seven studies that examined intakes of various supplements on skin structure and texture, four found significant improvements in skin 'roughness' [33,34,37,38] and three in skin elasticity [30,33,37]. Supplement intake from green tea and dietary supplements (with a variety of active ingredients) improved both skin elasticity and roughness whilst the intake of high flavonol cocoa improved skin roughness only [34].…”
Section: Skin Roughness and Elasticitymentioning
confidence: 99%
See 3 more Smart Citations